Survey of speech recognition approaches - Dehtiarov, D. (ХНУРЕ, 2019)
The aim of the work is to analyse modern interfaces and frameworks for application in developing the interface of language conversion into text. The main contribution of this work can be considered that at the moment in computer technologies the tasks of recognizing and understanding the context of speech are very relevant, since this can facilitate the way of communication between a person and a computer, these technologies are currently used in medical and military applications, security systems, automated systems for recognition and identification, etc.